La concurrence militaire dans les Chroniques de Froissart : une idéologie chevaleresque et son écriture - Clara de Raigniac (Les Cahiers de Framespa)
In this article, the notion of competition in the medieval military field shall be considered. A double restriction of the field is adopted: we will focus on a particular group of combatants, knighthood, and on the Hundred Years’ War as narrated in the Chronicles of Froissart. The two meanings of competition are thus combined; we talk about emulation when it is a question of attaining an all-personal chivalrous honor, but it can also become a dangerous rivalry within an army whose objective of common good is more and more prevalent. From a literary point of view, we will be interested in the poetics of competition developed by Froissart. Motifs such as the duet are used to construct, when reading, a competition-emulation between knights. Simultaneously, a topical writing of the united army is developed, with an insistence on order and the visual joy it evokes, inherited metaphors, a unifying figure of the chief.